NIMG-64. INTRAOPERATIVE LANGUAGE MAPPING USING GAMMA-BAND MODULATIONS OF ELECTROCORTICOGRAM (ECOG) INDUCED BY WORD/SOUND CATEGORIZATION TASK: VALIDATION WITH REPRODUCIBLE SPEECH ARRESTS DURING LINGUISTIC TASKS. (14th November 2022) - Tasnim, Israt; Ince, Nuri; Prabhu, Sujit; Noll, Kyle; Swamy, Chandra; Connelly, Katherine; Asman, Priscella; Sudhakar, Tummala; Prinsloo, Sarah; Ene, Chibawanye; Grasu, Roxana; Liu, Ho-Ling; et al.
Abstract: OBJECTIVE: Determination of the correlation between gamma-band modulations of electrocorticogram (ECoG) induced by linguistic tasks and reproducible speech arrests caused by bipolar direct cortical stimulations (DCS). METHODS: 3 subjects (age 39, 56, 64 years) with left temporal lobe glioma underwent surgery involving awake craniotomy. A 4x8 ECoG electrode grid (2.3mm contact exposure, 1cm contact spacing) was placed above the respective tumor area. A MATLAB-Simulink based real-time software system running on a portable laptop computer was used to map gamma-band modulations as a 2D heat map while the subjects engaged in different linguistic tasks: word/sound categorization by pressing a button, object naming, action naming, written descriptive naming, and auditory descriptive naming. Auditory stimulus was applied during word/sound categorization task (duration 300 – 500ms), auditory descriptive naming ( > 1s); other tasks involved visual stimulus only. The subjects repeated the four naming tasks while bipolar DCS (2/4/6 mA, 60Hz, 2s) was applied at different electrode pairs. RESULTS: The electrodes having stronger gamma-band modulations were distinct for different tasks. Reproducible speech arrests occurred during object, action, auditory naming tasks while stimulating specific electrode pairs, even though not all these electrodes had strong activations during these tasks. Across all subjects these electrodes had strong activations consistently during word/sound categorization tasks, starting as early as 250ms and lasting even after the auditory stimuli were terminated (~ 650ms). The longer activations can be associated with word recognition process. The subjects self-reported about having difficulty in comprehension rather than speech production during speech arrests. 3D brain rendering using MRI images showed that the speech arrest electrodes were identically located on the superior temporal gyrus, inferior to central sulcus for all 3 subjects. CONCLUSION: Intraoperative language mapping guided by gamma-band ECoG modulations induced by word/sound categorization tasks can be utilized to localize eloquent cortex associated with auditory processing.